A Summary Of Big Data Analytics In Electronic Commerce - Gampa, Kalpana; Madhukar, Vemula (Journal of Neonatal Surgery, 2025)
There are a number of problems with the widespread use of big data in online shopping, the most well-known of which being security. Businesses that deal in online sales are mainly concerned with how to establish a reliable method of risk assessment within the context of cloud computing.This study examines the security system of e-commerce and discusses the prevention of hidden security policies, bringing together data and e-commerce security. Presenting the Hadoop architecture through Apache Hadoop, this article analyses the YCSB benchmark with a focus on when e-commerce big data technology genuinely begins to address the problems with e-commerce security. The electronic security data perspective allows for the examination of the hidden e-commerce dangers and the successful enhancement of the e-commerce security system.